Determination of hypoglycaemia induced by insulin or its synthetic analogues post mortem. Issue 9 (11th July 2013) - Hess, C.; Madea, B.; Daldrup, T.; Musshoff, F.
Abstract : The determination of human insulin or its synthetic analogues in post‐mortem specimens represents a challenge for forensic toxicologists due to its proven instability in post‐mortem blood. We present two cases of an insulin‐induced hypoglycaemia. In the first case, ante‐mortem material was available for the detection of an injection with human insulin. Human insulin was detected by immunopurification with magnetic beads and liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) analyses at a concentration of 5180 μU/ml. The molar ratio human insulin:C‐peptide was 111. The second case describes a suicide by self‐injection of Insulin lispro and determination of the drug after pre‐extraction with methanol and immunopurification by LC‐MS/MS at the injection site, in vitreous humour and organs. Apart from the well‐known matrices – femoral blood and urine – the specimen vitreous humour and the injection site promise the best possibilities for a proof of insulin at autopsy. In addition to insulin analyses, the parameters C‐peptide, proinsulin, glucose, lactate, and sulfonylureas should be measured in case of suspected fatal hypoglycaemia. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Two cases of an insulin‐induced hypoglycaemia are presented, one injection with human insulin, another case with self‐injection of Insulin lispro . The possibility of detection of insulin and its synthetic analogues after pre‐extraction with methanol and immunopurification with magnetic beads and quantification by LC/MS‐MS in serum, at the injection site, in vitreous humor and organs is presented.